Desempenho técnico e econômico do policultivo da tilápia do nilo oreochromis niloticus (linnaeus, 1758) com camarão da Amazônia macrobrachium amazonicum (heller, 1862) - Maia, Cário Sheves Paiviandre (2011)
The commitment in to make an aquaculture in line with the concepts of sustainability, among many things, on use of polyculture systems and use of species that inhabit the water sources already in the vicinity of aquaculture ventures. Engaged in this context, the objective of this study was to evaluate the livestock development, productivity and economic performance of Nile tilapia Oreochromis niloticus and amazon river prawn Macrobrachium amazonicum in polyculture systems. The experiment was conducted in Aquaculture Department of the Universidade Federal Rural do Semi-Árido - UFERSA. The experimental design was completely randomized design with four treatments and four replicates. The treatments were: control treatment in monoculture of tilapia in the density of 2 animals m-2 (P2C0) and 3 treatments polyculture with tilápia densities of 2 m-2 and varying densities of shrimp 4, 8 and 16 animals m-2 (P2C4, P2C8 and P2C16). The initial values of individual mass of fingerlings and post larvae were 4,0g and 0,06g respectively. Were monitored physical-chemical parameters of water temperature, pH, dissolved oxygen, conductivity, turbidity, ammonia, nitrite, nitrate, orthophosphate and chlorophyll "a". The experiment lasted 150 days with total monthly samples of the animals, and the end of the experiment the main results: 92,48±7,4% survival (P2C0), 91,65±8,4% and 65,55±7,9% (P2C4), 91,63±4,3% and 77,29±18.6% (P2C8), 91,10±8,4% and 61,52±2,5% (P2C16); productivity 6601,65±479,5 kg ha-1 (P2C0), 6137,47±123,16 and 660,0±15,5 kg ha-1 (P2C4), 5951,52±648 and 210,08±45,2 kg ha-1 (P2C8), 6531,24±303,04 and 311,0±16,78 kg ha-1 (P2C16); economic returns 40,1±10.2%, 32,3±13.9%, 33,3±13,1% and 36,14±6,1% for P2C0, P2C4, P2C8 and P2C16 respectively. The use of M. amazonicum in polyculture with O. niloticus did not influence the economic return, proven to be a system technically feasible, but not increasing the economic viability when compared with monoculture